Villains are heroes today: iconographic notes on the prominence of evil in current media - González Torres, Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
It only takes a quick glance at movies, television series or video games to realize that we are being fed a massive dissemination of shocking images, violent acts and violations of classic standards. A plethora of representations of evil have become the protagonists by taking advantage of certain iconographies that make them look like heroes, thus developing an extraordinary potential for feeding their powerful egos. Our purpose is to highlight some of these archetypal features by considering a range of renowned productions. We intend to match the profles, functions and deeds of these characters to their infuences, the patterns they follow and the corruption lying behind their recognizable appearances, as well as the reasons for their personal crusades. In order to do this, we will be using the history of art, anthropology and sociology as main tools.